The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1111/j.1469-7998.1987.tb03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Past and present status of the southern elephant seal (Mirounga leonina) at Macquarie Island

Abstract: The southern elephant seal population at Macquarie Island has undergone a serious decline since regular surveys were commenced in 1949. Approximately 2,900 cows and 250 bulls were counted in the isthmus study area during the 1985 breeding season. Comparisons with 20 other counts made in the same area between 1949 and 1984 showed that, although there was considerable fluctuation between the years, the number of seals ashore has dropped at an average rate of 2.1% per year, resulting in a net decrease of approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 24 publications
1
73
2
Order By: Relevance
“…The colony analysed in this study is located at Isla 25 de Mayo, South Shetland Islands and corresponds to the South Georgia stock, in the Atlantic sector of the Southern Ocean. The population at South Georgia has remained stable over the past 45 years (mccann, 1985;hindell et al, 1987;lawS et al, 1994;Boyd et al, 1996;Burton et al, 1997;guinet et al, 1999;SCAR, 2002SCAR, , 2006mcmahon et al, 2003).…”
mentioning
confidence: 99%
“…The colony analysed in this study is located at Isla 25 de Mayo, South Shetland Islands and corresponds to the South Georgia stock, in the Atlantic sector of the Southern Ocean. The population at South Georgia has remained stable over the past 45 years (mccann, 1985;hindell et al, 1987;lawS et al, 1994;Boyd et al, 1996;Burton et al, 1997;guinet et al, 1999;SCAR, 2002SCAR, , 2006mcmahon et al, 2003).…”
mentioning
confidence: 99%
“…They require ample stored reserves obtained at sea to fuel their reproductive efforts on land. Declines occurred at key colonies in the Indian and Pacific sectors during the 1950s-1970s (13)(14)(15), whereas populations in the Atlantic sector remained stable (15)(16)(17). A recent reexamination concluded that changes in the marine environment were the most plausible cause of the observed declines (18).…”
mentioning
confidence: 99%
“…Across their distribution, the day the maximum number of females is hauled out varies from 2 October at Punta Delgada (42° 30'S) through 18 October at Heard Island (53°00'S) to 25 October at South Georgia (54° 19'S) and King George Island (62° 16'S) (Campagna et al 1993;Galimberti & Boitani 1999). The duration of the parturition period is reasonably consistent across their distribution at close to 60 days, and the number of females ashore approximates a Gaussian model (Hindell & Burton 1987;Galimberti & Boitani 1999). Small females tend to arrive earlier than large females, and the departure date is slightly more irregular than arrival.…”
Section: Reproductionmentioning
confidence: 94%
“…comm.). Preweaning mortality was around 5% (Hindell & Burton 1987;McMahon et al 1999b). By contrast, on Marion Island, where the population declined at 2.5% a year from 1986 to 1991, and 4.3% from 1991-1997, survivorship from 1-3 years was only 69% for males and 74% for females; from 4-9 years, male survivorship was 66% and female 75% (Pistorius et al 1999).…”
Section: Age and Mortalitymentioning
confidence: 97%
See 1 more Smart Citation